356. A CASE REPORT: A CASE OF HIATAL HERNIA WITH UPSIDE-DOWN STOMACH TREATED WITH LAPAROSCOPIC SURGERY. (24th September 2022) - Uemura, Takuji; Morishima, Rento; Kanai, Norifumi; Yoshida, Satoru; Yonaiyama, Shinnosuke; Maruyama, Shota; Nakayama, Yoshihito; Nishimura, Ryuichi; Sato, Tomoyuki; Aoki, Kazunori; Mizuno, Yutaka
Abstract: Upside-down stomach (UDS) is a rare type (<5%) of hiatal hernia, often accompanied by organoaxial gastric volvulus. Although surgery is required for most patients, approach method is still controversial. It has been reported that open approach is a standard method in the case of UDS, but recently laparoscopic approach is reported to be useful for the patient without stomach ischemic sign. Here we report the case of UDS successfully treated by laparoscopic surgery. Case presentation: A 57 year-old male patient with hiatal hernia for several years was referred to our institution because of frequent vomiting and UDS. He had no pain and vital signs were stable. Hematological investigations revealed neutrophil dominant elevation of white blood cell count, but CRP was normal in blood biochemistry. An enhanced computed tomography revealed a giant hiatal hernia (Type IV) and whole stomach migrated into posterior mediastinum with organoaxial gastric volvulus, but obviously ischemic signs were not detected. An esophagogastoroduodenoscopy (EGD) showed erosion of gastric mucosa, but no necrotic sign of stomach. From these findings, surgery was thought to be necessary to improve the obstruction of stomach and prevent from necrosis of the incarcerated stomach. However, because of stable general conditions and no ischemic findings, we performed laparoscopic repair of hiatal hernia and Toupet fundopulication. Ischemic change of the stomach was not observed. After stomach withdrawal into the abdominal cavity from the mediastinum, hiatal defect was repaired and fundoplication was performed by Toupet method. After surgery, the symptom and stomach passage obstruction improved and the patient was discharged without no complications. We successfully performed hiatal hernia repair and fundopulication with laparoscopic approach in the case of UDS. If there are no findings obviously indicating gastric ischemia and necrosis on an enhanced computed tomography and an EGD, laparoscopic hiatal hernia repair and fundoplication are considered as a useful method because of its less invasiveness and magnifying effect.